Living donor age and kidney transplant outcomes: an assessment of risk across the age continuum. (6th February 2013) - Sapir‐Pichhadze, Ruth; Young, Ann; Joseph Kim, S.
Summary Detailed data on living donor age, and its interplay with recipient age, in predicting allograft and recipient outcomes are wanting. We used the Scientific Registry of Transplant Recipients (2000–2009, n = 49 589) to assess the effect of living donor age on delayed graft function (DGF), total graft failure, death‐censored graft failure, death with graft function, and graft failure with death as a competing risk using logistic and Cox proportional hazards models. Potential nonlinear associations were modeled using fractional polynomial functions. There was a significant 1.87‐fold increase in the adjusted odds of DGF in the oldest versus youngest age groups. The 10‐year adjusted hazard ratios (HR) for total graft failure, death‐censored graft failure, and death with graft function increased in a nonlinear fashion across the range of living donor age studied. Graft failure was most accentuated in the youngest recipient age groups in competing risk models. Adjustment for renal function at 6‐ and 12‐months post‐transplant markedly attenuated the association between living donor age and graft/patient outcomes. Our findings confirm the important influence of living donor age on transplant outcomes and provide detailed estimates of risk across the living donor age continuum.